Drinking water vulnerability to climate change and alternatives for adaptation in coastal South and South East Asia - Hoque,MA; Scheelbeek,PFD; Vineis,P; Khan,AE; Ahmed,KM; Butler,AP (Climatic Change, 2016)
Drinking water in much of Asia, particularly in coastal and rural settings, isprovided by a variety of sources, which are widely distributed and frequently managed atan individual or local community level. Coastal and near-inland drinking water sources inSouth and South East (SSE) Asia are vulnerable to contamination by seawater, mostdramatically from tropical cyclone induced storm surges. This paper assesses spatialvulnerabilities to salinisation of drinking water sources due to meteorological variabilityand climate change along the (ca. 6000 km) coastline of SSE Asia. The risks of increasingclimatic stresses are first considered, and then maps of relative vulnerability along theentire coastline are developed, using data from global scale land surface models, alongwith an overall vulnerability index. The results show that surface and near-surfacedrinking water in the coastal areas of the mega-deltas in Vietnam and Bangladesh-Indiaare most vulnerable, putting more than 25 million people at risk of drinking ‘saline’ water.Climate change is likely to exacerbate this problem, with adverse consequences for health,such as prevalence of hypertension and cardiovascular diseases. There is a need foridentifying locations that are most at risk of salinisation in order for policy makers andlocal officials to implement strategies for reducing these health impacts. To counter therisks associated with these vulnerabilities, possible adaptation measures are also outlined.